Cystoid Macular Edema after cataract correction surgery, a case report (Research, Society and Development, 2022)
The main objective of the study was to report the case of a 75-year-old patient diagnosed with progressive low visual acuity in the right eye after cataract surgery. In the ophthalmological examination, performed at the Ophthalmological Hospital of Araraquara, cystoid macular edema was observed in the right eye associated with the presence of vitreous beams towards the incision. A treatment, for cystoid macular edema, the use of non-steroidal anti-inflammatory topic drugs and topical corticosteroids has been proposed. For the treatment of the glass beams, vitrectomy with the use of a Yag Laser was proposed. It is concluded that both treatments contributed to a positive result, demonstrated by the complete resolution of the cystic intraretinal fluid after one month of treatment with topical medication and resolution of the glass beams after vitreo lysis with the use of the Yag Laser. This fact significantly contributed to the increase in the patient's visual acuity and improved quality of life.